2015
DOI: 10.3109/0284186x.2015.1067720
|View full text |Cite
|
Sign up to set email alerts
|

A method for evaluation of proton plan robustness towards inter-fractional motion applied to pelvic lymph node irradiation

Abstract: Background. The benefi t of proton therapy may be jeopardized by dose deterioration caused by water equivalent path length (WEPL) variations. In this study we introduced a method to evaluate robustness of proton therapy with respect to inter-fractional motion and applied it to irradiation of the pelvic lymph nodes (LNs) from different beam angles. Patient-versus population-specifi c patterns in dose deterioration were explored. Material and methods. Patient data sets consisting of a planning computed tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Only the beam angles that are used for treatment can then be analyzed for differences. Another application of using the WEPL estimations was presented for robust optimization of proton therapy planning [29,30]. For proton therapy the water equivalent path length is of utmost importance to determine the range of the proton beams making such a WEPL based decision criteria an attractive method for patient treatment verification.…”
Section: Discussionmentioning
confidence: 99%
“…Only the beam angles that are used for treatment can then be analyzed for differences. Another application of using the WEPL estimations was presented for robust optimization of proton therapy planning [29,30]. For proton therapy the water equivalent path length is of utmost importance to determine the range of the proton beams making such a WEPL based decision criteria an attractive method for patient treatment verification.…”
Section: Discussionmentioning
confidence: 99%
“…configuration was sensitive towards inter-fractional motion, causing target underdosage [24]. However in another study of pelvic LN irradiation with protons, lateral oblique fields were found robust towards density changes [14].…”
Section: Discussionmentioning
confidence: 97%
“…Two IMPT plans using multi-field optimisation were created (Eclipse treatment planning system (TPS), Varian Medical Systems, Palo Alto, CA, USA) on the pCT, with one using two lateral opposed beams (gantry angles 90°/270°) and the other using two lateral oblique beams (gantry angles 35°/325°) identified in a previous inter-fractional robustness study [14] (Suppl. Fig.…”
Section: Treatment Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Several prior studies have examined the robustness of proton therapy plans for patients receiving radiotherapy to the prostate, seminal vesicles, and/or the pelvic lymph nodes [16][17][18][19][20]. The results of these studies have identified strategies to optimize proton therapy delivery through selection of beam angles less sensitive to patient setup error, modification of planning optimization techniques, or patient alignment strategies that minimize displacement of internal pelvic anatomy (e.g.…”
Section: Discussionmentioning
confidence: 99%